Analisis Cacat Produk pada Line Produksi Mesin IDAH dengan Metode Seven Tools dan Kaizen - Arya Bagus Rizkyllah; Yekti Condro Winursito (Jurnal Serambi Engineering, 2025)
Defective products are goods or services that are produced in the production process but have defects that cause their quality to be poor. The aim of this research is to discuss the causes of failed or defective feed products. The research method used is Seven Tools and Kaizen. From the defect data, it was found that the largest contributor to the number of defects from the total production of 161,040 kg of defective fish feed was striped colour, amounting to 143,760 kg or 89.27%, while moist > std of 17,280 kg or 10.73%. The analysis results show that stripe colour defects are a top priority to be minimised. The problem is solved by human, machine and environmental factors in the form of arranging production work time schedules, carrying out nozzle spray checks periodically, replacing the pusher fluid on the machine and adding lighting to the analysis area to check product defects.